Fluoride release by glass ionomer cements, compomer and giomer - Sayed Mostafa Mousavinasab; Ian Meyers (Dental Research Journal, 2009)
Background:To measure the amounts of fluoride released from fluoride-containing materials, four glass ionomer cements (Fuji IX, Fuji VII, Fuji IX Extra and Fuji II LC), a compomer (Dyract Extra) and a giomer (Beautifil) were used in this study. Methods:Twenty cylindrical specimens were prepared from each material. The amount of released fluoride was measured during the first week and on the days 14 and 21 by using specific fluoride electrode and an ionanalyzer. The results were statistically analyzed using analysis of variance (two-way ANOVA) and Tukey Kramer multiple comparison tests (p=0.05). Results:Significant differences were seen in fluoride release of different days and materials (p<0.05). The maximum cumulative fluoride release of days 1-7 was related to Fuji VII, followed by Fuji IX Extra, Fuji II LC, Fuji IX, Dyract Extra and Beautifil in descending order and this order re-mained the same until the 21st day. Conclusion:Fuji IX, Fuji VII, Fuji IX Extra, and Fuji II LC released higher amounts of fluoride compared to Beautifil and Dyract Extra in this study. It seems that the extent of the glass ionomer matrix plays an important role in determining the fluoride releasing ability of glass ionomer cement materials.